Sequences of epicuticular wax structures along stems in four selected tree species - Tomaszewski, Dominik; Zieliński, Jerzy (Biodiversity: Research and Conservation, 2015)
Very rapid production of prominent wax crystals was observed in stems. In an experiment involving mechanical wax removal from the A. negundo stem surface and subsequent analysis of the surface after several days via scanning electron microscopy (SEM), it was shown that wax regenerates very quickly. After only several hours, new emerging crystals were observed and their morphologies were essentially the same. Nearly full regeneration was observed several days after removal.